22 Transcatheter aortic valve replacement: a comparison of the direct flow medical and sapien 3 aortic valves. (24th April 2016) - Jabbar, Avais; Mohammed, Ashfaq; Khurana, Ayush; Das, Rajiv; Zaman, Azfar; Edwards, Richard
Abstract : Introduction: The Direct Flow Medical (DFM) valve is a non-metallic, double ring valve which is repositionable and retrievable. The Freeman Hospital is the highest volume DFM centre in the UK. We wanted to compare the safety of this valve with the Sapien 3 (S3) TAVR valve. Methods: We retrospectively assessed all the S3 and DFM TAVR procedures performed under general and local anaesthetic. Of 71 patients, 44 had the S3 valve inserted and 27 had the DFM valve inserted. The delivery approach was trans-femoral in all patients. Results: Both groups were similar with respect to age, comorbidities, and EuroScore. The severity of aortic stenosis was significantly greater in the S3 group pre procedure. Skin open to skin closure was significantly shorter in the S3 group (145 mins vs 101 mins; p < 0.001). There were no deaths or strokes in either group. 1 patient in the DFM group needed permanent pacing post procedure. 1 patient in the DFM group developed moderate aortic regurgitation. The mean gradient and peak gradient was significantly higher in the DFM group post procedure (17.9 vs 12.3; p = 0.016, and 31.1 vs 23.8mmHg; p = 0.013). There was no relationship between the size of the valve and the peak gradient using regression analysis in both groups (p = 0.181 and p = 0.44). There was no difference in the mean number of days in hospital between both groups (2.6 vs 2.8; p = 0.47). Conclusions: There were no differences in safety between the Sapien 3 and DFM valves although we found the mean and peak gradients to be significantly higher with the DFM valve post procedure.